IMPLICATIONS OF DEFENCE RESOURCE MANAGEMENT ON NATIONAL OBJECTIVES - BORDEA, Simona-Daniela (Strategic Impact, 2023)
The new international context justifies an analysis of the priorities, interests and objectives of the Pontic states in relation to an immediate reaction to discourage the armed conflict initiated by Russia and unjustified in terms of international humanitarian law. NATO and the EU have recently intensified the conduct of large-scale maritime exercises to promote stability and peace and strengthen the Alliance’s Eastern Flank, and have consistently encouraged cooperation between outgoing states on the Black Sea. Although Russia’s energy dependence on some Pontic states could be a problem for the mutual agreement on strategic negotiations and partnerships, NATO and the EU must join forces to take concrete and deterrent action to maintain regional and international order alike. The present article aims to highlight the importance of the Black Sea for the Pontic states, having as the premise of the scientific research the fact that nowadays it represents an important cross-border resource both for the security of the states in the region and for the security of NATO and the EU.